MUSIC CONCERT PROMOTERS’ CHALLENGES TO ACHIEVE SUSTAINABLE EVENTS FOR SDGS - Dian Elvira; Luki Adiati Pratomo (Journal of Social Research, 2023)
The Sustainable Development Goals provide an opportunity for each industry to move towards sustainability. To increase awareness of sustainability issues, event promoters encounter various challenges in planning and organizing sustainable music concerts. This study aims to identify the challenges of achieving sustainable events in organizing two music concerts held in Jakarta, Indonesia from the promoters’ perspective as an effort towards the Sustainable Development Goals. This study used a qualitative approach. A semi-structured interview was conducted with 10 stakeholder representatives to find out the role of decision-makers in planning music concerts. Documents and information from the organizers were used to complete the qualitative analysis. The results showed that sustainable events cannot be applied comprehensively in organizing music concerts. There were obstacles from external and internal promoters in their preparation which affected the decision-making so that they became factors hindering the implementation of sustainable principles in organizing music concerts. The challenges for promoters in preparing for music concerts are the ignorance of stakeholders regarding the environmental impacts, the unprepared facilities, infrastructures to support sustainability, and socialization to achieve sustainable development goals. This research contributes to policymakers by revealing promoter barriers to sustainable events for achieving sustainable development goals.